FVM model and virtual instrument based system for electromagnetic characterization of steel material - El Ghoul, Islam-Ncereddine; Cheriet, Ahmed; Bensaid, Samir; Lakhdari, Ala-Eddine (Journal of Applied Engineering Science & Technology, 2016)
This paper deals with a finite volume model and virtual instrument based system for electromagnetic characterization of steel material. Both magnetic permeability and electrical conductivity are electromagnetic properties must be defined. These two parameters are strongly required for electromagnetic problems analysis such as in eddy current nondestructive testing problem. The magnetic permeability is measured by using the B(H) loop of the steel material which is illustrated by experimental measurement through a virtual instrument based system. However, the electrical conductivity is obtained by the solution of an inverse problem. For that reason a direct electromagnetic model is analyzed using the finite volume method.
Keywords: FVM; Labview; Magnetic permeability; Electrical conductivity; Steel